Sustainable Energy Planning and Management – SDEWES 2024 Special Issue on transition from coal and modelling approaches - Østergaard, Poul Alberg; Duic, Neven (International Journal of Sustainable Energy Planning and Management, 2025)
This 45th volume of the International Journal of Sustainable Energy Planning and Management includes papers from the Sustainable Development of Energy, Water and Environmental Systems (SDEWES) conference series held in 2024. A focus area of this special issue is conversion of coal-reliant energy systems in Columbia, Indonesia and Poland. Another focus area is on modelling approaches and the inclusion of decision makers and stakeholders in the process.